Islamic inheritance law and its application in the Republic of Singapore : an analytical study on joint-tenancy - Nur Aamal binti Arif (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The study on Islamic inheritance law and its application in the Republic of Singapore aims to highlight the importance of estate distribution in accordance to Islamic jurisprudence. It is inevitable that Muslims need to comprehend and implement the Islamic inheritance law in managing their properties and estates. To understand the matters further, clarification and examples of the calculation related to Islamic inheritance law are included in this study. Apart from that, this study attempts to analyze the issues faced by Muslims in Singapore regarding joint-tenancy which its context of ownership between the Civil law and MUIS Fatwā is in contradiction. The suggestions from the Fatwā Committee on Hibah al-Ruqbā and Nudhriyah as the tools in transferring the deceased's estate in joint-tenancy contract are discussed in this research with the views of Muslim scholars on the issues. This study adopts a qualitative methodology in collecting reliable data from articles, websites, books, treaties and writings of classical and contemporary jurists and scholars. In addition, data on joint-tenancy in the light of Islamic inheritance law as well as Hibah al-Ruqbā and Nudhriyah were collected from interviews and seminars.The study concludes with the view that there is a need to make documented agreement in dealing with joint-tenancy contract in order to give clarification on the ownership of the property.